FACTORS RELATED TO THE ROLE OF HEALTH OFFICIALS IN SUPERVISING POST PARTUM PERIOD OF KUTA COT GLIE HEALTH CENTER ACEH BESAR - Arbi, Anwar; Liana, Intan (Poltekkes Kemenkes Jambi, 2019)
Background: Adequate health monitoring and care during pregnancy until the postpartum period is very important for the survival of the mother and her baby. Efforts to accelerate the reduction of maternal mortality in reducing the availability of maternal health services in the community. The purpose of the study was to determine the factors associated with the role of health workers in monitoring the postpartum period in the Kuta Cot Glie Community Health Center Working Area in Greater Aceh District in 2018. Methods: This study was descriptive analytic with a cross-sectional approach. The population in this study were all midwives in the Kuta Cot Glie Community Health Center Working Area. A total of 36 midwives, recruited using total sampling technique. The hypothesis of this study was analysed using chi square test. Results: It was found that there was a relationship between information media (p-value 0.048), attitudes of health workers (p-value 0.001), and access to health workers (p-value 0.008). Conclusion: A relationship were found between media information, attitudes of health workers, access to health workers in the supervision of the puerperium.